Evaluation of dystonia in children and adolescents treated with atomoxetine within the Truven MarketScan database: a retrospective cohort study. Issue 5 (4th May 2018) - Meyers, Kristin J.; Upadhyaya, Himanshu P.; Goodloe, Robert; Kryzhanovskaya, Ludmila A.; Liles-Burden, Marie A.; Kellier-Steele, Nicole A.; Mancini, Michele
ABSTRACT: Objective : Atomoxetine is a non-stimulant drug indicated for the treatment of attention-deficit/hyperactivity disorder in children aged ≥6 years, adolescents, and adults. In this retrospective cohort study, the incidence and risk of dystonia in children and adolescents treated with atomoxetine was compared to a propensity score-matched cohort of stimulant users. Methods : Data between 1 January 2006 and 31 December 2014 from patients aged 6–17 years in the Truven Health Analytics MarketScan database were used to generate two cohorts of patients: (1) atomoxetine users and (2) stimulant (methylphenidates or amphetamines) users. A Cox proportional hazards regression model was used to compare incidence of dystonia across propensity score-matched cohorts. Results : Of the 70, 657 atomoxetine users, 70, 655 users were propensity score-matched to a stimulant user. In the atomoxetine- and stimulant-treated cohorts, the crude incidence rates of dystonia were 54.9 (95% CI: 27.1–82.7) and 77.9 (95% CI: 49.1–106.8) per 100, 000 person-years, respectively. The hazard ratio for occurrence of dystonia with atomoxetine use relative to stimulant use was 0.68 (95% CI: 0.36 − 1.28; P = 0.23). Conclusion : In this large retrospective cohort study, there was no significant difference in incidence or risk of dystonia among patients treated with atomoxetine compared to stimulants.